The impact of formulation attributes and process parameters on black seed oil loaded liposomes and their performance in animal models of analgesia - Zerin T. Rushmi; Nasrin Akter; Rabeya J. Mow; Merina Afroz; Mohsin Kazi; Marcel de Matas; Mahbubur Rahman; Mohammad H. Shariare (Elsevier, 2017)
This study aimed to formulate black seed oil (Nigella sativa) loaded liposomes using the ethanol injection method to enhance oral bioavailability and improve therapeutic activity in small animal studies of analgesia. The impact of formulation attributes and process parameters on the liposomal system was evaluated with key quality attributes being particle size, morphology, and entrapment efficiency. The particle size and entrapment efficiency of the liposome preparation were found to be between the range of 50-900 nm and 34-87% respectively. Particle size distribution data suggested that increasing the percentage of oil, up to a certain concentration, reduced the size of the liposomes significantly from 520 ± 81.2 nm to 51.48 ± 1.31 nm. Stirring and injection rate were shown to have marked impact on the average particle size of liposome. It was observed that entrapment efficiency of liposomes was greatly influenced by the amount of cholesterol and type of cryoprotectant used during formulation. The stability study indicated that the liposomal preparation was stable at ambient conditions for one month. In vivo studies showed that the liposomal preparation demonstrated significant analgesic activity in mice.